The stomachache - Jaywant, Sheela (Research and Humanities in Medical Education, 2021)
This is a story about a person who gets plenty of advice from neighbours/relatives/friends to 'cure' his stomacheache. Going to a hospital is difficult and expensive. He wants relief from symptoms, not a cure.